Efecto de extractos de artrópodos sobre la multiplicación del Toxoplasma gondii dentro de macrófagos peritoneales de ratón - Chinchilla Carmona, Misael (Universidad de Costa Rica, 2003)
Treatment of toxoplasmosis usually causes secondary effects. It is important to find active substances extracted from natural organisms. In this work we studied some arthropod extracts that have effect against Toxoplasma multiplication inside mouse macrophages. After studying 382 extracts, 23 were selected on the basis of the activity and we found that 13 extracts from orders Polydesmida, Lepidoptera, Orthoptera and Hymenoptera exerted an important inhibition of Toxoplasma multiplication.